MicroRNA-182-5p Attenuates Asthmatic Airway Inflammation by Targeting NOX4 - Wang, Zhiguang; Song, Yilan; Jiang, Jingzhi; Piao, Yihua; Li, Li; Bai, Qiaoyun; Xu, Chang; Liu, Hanye; Li, Liangchang; Piao, Hongmei; Yan, Guanghai (Frontiers in Immunology, 2022)
Bronchial asthma is characterized by chronic airway inflammation, airway hyperresponsiveness, and airway remodeling. MicroRNA (miRNA) has recently been implicated in the pathogenesis of asthma. However, the mechanisms of different miRNAs in asthma are complicated, and the mechanism of miRNA-182-5p in asthma is still unclear. Here, we aim to explore the mechanism of miRNA182-5p in asthma-related airway inflammation. Ovalbumin (OVA)-induced asthma model was established. MiRNA Microarray Analysis was performed to analyze the differentially expressed miRNAs in the asthma model. We found that the expression of miRNA-182-5p was significantly decreased in OVA-induced asthma. In vitro, IL-13 stimulation of BEAS-2B cells resulted in a significant up-regulation of NOX4 (nicotinamide adenine dinucleotide phosphate oxidase 4), accompanied by mitochondrial damage-induced apoptosis, NLRP3 (NOD-like receptor family pyrin domain-containing 3)/IL-1β activation, and reduced miRNA-182-5p. In contrast, overexpression of miRNA-182-5p significantly inhibited epithelial cell apoptosis and NLRP3/IL-1β activation. In addition, we found that miRNA-182-5p could bind to the 3’ untranscripted region of NOX4 mRNA and inhibit epithelial cell inflammation by reducing oxidative stress and mitochondrial damage. In vivo, miRNA-182-5p agomir treatment significantly reduced the percentage of eosinophils in bronchoalveolar lavage fluid, and down-regulated Th2 inflammatory factors, including IL-4, IL-5, and OVA induced IL-13. Meanwhile, miRNA-182-5p agomir reduced the peribronchial inflammatory cell infiltration, goblet cell proliferation and collagen deposition. In summary, targeting miRNA-182-5p may provide a new strategy for the treatment of asthma.